Expermental research of the effects of benofilin on the functional renal function in the evalution of ethylene glycol toxic loss - Matviychuk, O. P.; Matviychuk, A. V.; Taran, A. V. (Journal of Education, Health and Sport, 2019)
Effect of benofilin – a new compound among a new derivative of theophylline and hofitol (70 mg/kg) on functional renal function was studied based on the rat experimental model of acute kidney damage by ethylene glycol. The toxic products of the metabolism of ethylene glycol cause renal tubular damage resulting in acute renal failure (ARF). As a result of the application of benofilin its ability is established to prevent the death of animals in the first day of the experiment. By the ability to prevent impaired kidney function in rats benofilin exceeds the effect of the hofitol.